A method for electrodepositing copper-nickel alloy foil by using a complex salt of organic phosphonic acid and citric acid

CN122898936APending Publication Date: 2026-10-13GANNAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611404094.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0006]本发明的目的在于提供一种有机膦酸与柠檬酸复合盐络合体系电沉积铜镍合金箔的方法,以解决目前电沉积制备铜镍合金箔时存在厚度均匀性差、表面粗糙度高和耐腐蚀性能差的问题

Benefits of technology

[0019](1)本发明构建了一种由羟基乙叉二膦酸二钠、柠檬酸钠、焦磷酸钾和四硼酸钠复配的四元复合络合体系。其中,羟基乙叉二膦酸二钠分子中的双膦酸基团对铜离子表现出较强的配位络合能力,可将亚铜离子中间体牢固地稳定在络合态,从反应源头大幅抑制歧化副反应的发生;柠檬酸钠对镍离子具有适中的络合强度,兼顾了镍离子的稳定络合和有效放电,保障了铜镍共沉积的顺利实现;焦磷酸钾和四硼酸钠分别从离子强度维持和pH缓冲两个维度强化镀液的长期运行稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898936A_ABST
    Figure CN122898936A_ABST
Patent Text Reader

Abstract

The application relates to a method for electrodepositing copper-nickel alloy foils by using an organic phosphonic acid and citric acid complex salt complex system, and belongs to the technical field of metal alloy materials. The application constructs a quaternary complexing system which is compounded by disodium hydroxyethylidene diphosphonate, sodium citrate, potassium pyrophosphate and sodium tetraborate. The biphosphonic acid group in the disodium hydroxyethylidene diphosphonate molecule shows strong complexing capacity for copper ions, can firmly stabilize the cuprous ion intermediate in a complex state, and greatly inhibits the occurrence of disproportionation side reactions from the reaction source; the sodium citrate has moderate complexing strength for nickel ions, and can realize the stable complexing and effective discharge of the nickel ions, so that the copper-nickel co-deposition is smoothly realized; the potassium pyrophosphate and the sodium tetraborate respectively strengthen the long-term operation stability of the plating solution from the two dimensions of ion intensity maintenance and pH buffering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for electrodepositing copper-nickel alloy foil using an organophosphonic acid and citric acid composite salt complex system, belonging to the field of metal alloy materials technology. Background Technology

[0002] Copper-nickel alloy foil, with its excellent resistance to seawater corrosion, good processability, and silvery-white metallic luster, plays an irreplaceable role in marine equipment, precision instruments, electromagnetic shielding, and high-end decoration. Electrodeposition technology is the mainstream preparation route for achieving thinner and higher-performance copper-nickel alloy foil. However, the industrialization of this technology has always been constrained by two core challenges: First, the standard electrode potentials of copper and nickel differ significantly. Under conventional electrodeposition conditions, copper ions preferentially discharge and deposit, easily causing the nickel content in the coating to deviate from the target composition. Macroscopically, this manifests as large fluctuations in foil thickness and severe compositional segregation. Second, during the electrodeposition process, copper ions undergo stepwise reduction. The intermediate product, cuprous ions, inevitably undergoes a disproportionation reaction in the plating bath, generating a large amount of fine copper powder. This copper powder not only wastefully consumes copper ions in the plating bath but also becomes a corrosion initiation point and a mechanically weak area after being incorporated into the coating, severely degrading the surface quality and service performance of the copper-nickel alloy foil.

[0003] To address the potential matching challenge in copper-nickel co-deposition, existing technologies generally employ the introduction of complexing agents into the plating bath to adjust the deposition potential of metal ions. Pyrophosphate is one of the most widely used complexing agents, exhibiting significant complexing and stabilizing effects on both copper and nickel ions. However, plating bath systems relying solely on pyrophosphate have limited stabilizing ability for cuprous ions during long-term electrodeposition, making it difficult to effectively suppress the disproportionation reaction. As the plating bath ages, the bath gradually becomes turbid, the tank voltage continuously drifts, and the resulting coating surface becomes rough with deteriorated mechanical properties. While hydroxycarboxylate complexing agents, such as citrate and tartrate, possess certain auxiliary complexing and pH buffering functions, their complexing stability constants for copper and nickel ions are low, making them unable to independently maintain the copper-nickel co-deposition potential. Consequently, the uniformity and density of the obtained coating are unsatisfactory. Furthermore, although sodium tetraborate, as a pH buffer, can mitigate the acidification trend of the plating bath, its inhibitory effect on the core side reaction of cuprous ion disproportionation is minimal.

[0004] Regarding functional additives, sulfur-containing organic compounds with sulfonic acid groups, such as sodium 3-mercapto-1-propanesulfonate (MPS) and sodium 3-(2-benzothiazolyl-mercapto)propanesulfonate (ZPS), can generate a certain polarization effect on the cathode surface, contributing to the refinement of coating grains, but their ability to inhibit disproportionation reactions is limited. While disulfide compounds such as disodium bis(3-sulfopropyl)bis(benzothiazolyl-2-yl)disulfide have superior leveling effects, they also suffer from the functional defect of not being able to effectively stabilize cuprous ions.

[0005] In summary, there is an urgent need to develop a method for electrodepositing copper-nickel alloy foil that can improve the thickness uniformity, mechanical properties, and corrosion resistance of the copper-nickel alloy foil. Summary of the Invention

[0006] The purpose of this invention is to provide a method for electrodepositing copper-nickel alloy foil using an organophosphonic acid and citric acid composite salt complex system, in order to solve the problems of poor thickness uniformity, high surface roughness, and poor corrosion resistance in the current electrodeposition preparation of copper-nickel alloy foil.

[0007] This invention provides a method for electrodepositing copper-nickel alloy foil using an organophosphonic acid and citric acid complex salt system, comprising the following steps: placing an anode plate and a cathode plate in a deposition electrolyte for electrodeposition to obtain a copper-nickel alloy foil on the cathode plate; the deposition electrolyte is prepared by mixing copper sulfate, nickel sulfate, disodium hydroxyethylidene diphosphonate, sodium citrate, potassium pyrophosphate, sodium tetraborate, sodium saccharin, additives, and water; the chemical structure of the additives is as follows:

[0008] .

[0009] Preferably, in the deposition electrolyte, the concentrations are as follows: copper sulfate 0.025-0.05 mol / L, nickel sulfate 0.12-0.15 mol / L, disodium hydroxyethylidene diphosphonate 0.03-0.05 mol / L, sodium citrate 0.12-0.18 mol / L, potassium pyrophosphate 0.12-0.18 mol / L, sodium tetraborate 0.015-0.025 mol / L, sodium saccharin 0.8-1.5 g / L, and additives 0.1-0.4 g / L.

[0010] Preferably, the electrodeposition process parameters are: the temperature of the deposition electrolyte is 55~65℃, the stirring speed is 350~450rpm, and the current density is 0.8~1.2A / dm³. 2 .

[0011] Preferably, during electrodeposition, a titanium plate is used as the cathode, and a phosphor bronze plate and a nickel plate are used as the anode.

[0012] Preferably, the area ratio of the phosphor bronze plate to the nickel plate in the anode is 2~4:1.

[0013] Preferably, the preparation method of the additive includes the following steps: 2-bromoethylphosphonic acid is mixed with potassium carbonate and potassium iodide in N,N-dimethylformamide to generate potassium phosphonate salt, and then benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine is added to react. The reaction product is acidified, washed, and dried to obtain a bisphosphonic acid intermediate; the bisphosphonic acid intermediate is mixed with sodium 2-bromoethylsulfonate, potassium carbonate, and potassium iodide in N,N-dimethylformamide containing water to obtain the additive.

[0014] Preferably, the molar ratio of 2-bromoethylphosphonic acid, potassium carbonate, and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine is 2~2.1:3~3.5:1.

[0015] Preferably, the reaction temperature for adding benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine is 90~100℃, and the reaction time is 10~14h.

[0016] Preferably, the molar ratio of the bisphosphonic acid intermediate, sodium 2-bromoethylsulfonate, and potassium carbonate is 1:2.2~2.3:1.5~2.

[0017] Preferably, the reaction of the bisphosphonic acid intermediate with sodium 2-bromoethylsulfonate, potassium carbonate and potassium iodide in N,N-dimethylformamide containing water is carried out at a temperature of 80-90°C for 10-14 hours.

[0018] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0019] (1) This invention constructs a quaternary composite complex system composed of disodium hydroxyethylidene diphosphonate, sodium citrate, potassium pyrophosphate, and sodium tetraborate. Among them, the bisphosphonic acid group in the disodium hydroxyethylidene diphosphonate molecule exhibits a strong coordination complexing ability for copper ions, which can firmly stabilize the cuprous ion intermediate in the complex state and significantly suppress the occurrence of disproportionation side reactions from the reaction source; sodium citrate has a moderate complexing strength for nickel ions, taking into account both the stable complexing and effective discharge of nickel ions, ensuring the smooth realization of copper-nickel co-deposition; potassium pyrophosphate and sodium tetraborate enhance the long-term operational stability of the plating solution from the two dimensions of maintaining ionic strength and pH buffering, respectively.

[0020] (2) This invention synthesizes a novel bifunctional additive (benzisothiazolyl bisphosphonate disulfonic acid hexasodium salt) with benzo[1,2-d:4,5-d']bis(thiazolium)-2,6-diamine as a rigid backbone and phosphonic acid and sulfonic acid groups grafted at both ends, respectively. This additive molecule integrates the "anti-disproportionation" function of the phosphonic acid group and the "cathodic polarization-grain refinement" function of the sulfonic acid group onto the same molecular platform with a fixed spatial spacing, achieving in-situ synergy of the two key functions. Experimental data show that, compared with a simple physical mixture of phosphonic acid and sulfonic acid functional molecules, the bifunctional integration on the same molecule can significantly improve the tensile strength of the coating and the stability of the plating solution.

[0021] (3) This invention utilizes a quaternary composite complex system combined with bifunctional additives to electrodeposit copper-nickel alloy foils possessing high strength, high toughness, and excellent corrosion resistance. The prepared alloy foils exhibit tensile strengths of 685–719 MPa, elongation of 6.0–6.6%, surface roughness Ra as low as 0.07–0.11 μm, and corrosion current density of 1.57–1.82 μA / cm² in a 3.5 wt.% sodium chloride solution. 2 Meanwhile, the voltage fluctuation of the plating bath during the 72-hour continuous electroplating experiment was less than 1V, indicating that the plating solution system has excellent resistance to degradation and the potential for industrial continuous production. Attached Figure Description

[0022] Figure 1 The above is the 1H NMR spectrum of the bisphosphonic acid intermediate prepared in Example 1 of this invention;

[0023] Figure 2 This is the 1H NMR spectrum of the additive prepared in Example 1 of the present invention. Detailed Implementation

[0024] The following examples are intended to further illustrate the content of the present invention, rather than to limit the scope of protection of the present invention.

[0025] Example 1

[0026] The method for electrodepositing copper-nickel alloy foil using an organophosphonic acid and citric acid composite salt complex system in this embodiment includes the following steps:

[0027] (1) Copper sulfate and nickel sulfate were dissolved in deionized water to obtain a mixed solution of copper sulfate and nickel sulfate (the concentrations of copper sulfate and nickel sulfate in the mixed solution were 0.20 mol / L and 0.75 mol / L, respectively); disodium hydroxyethylidene diphosphonate, sodium citrate, potassium pyrophosphate, and sodium tetraborate were added to deionized water, heated to 45~50℃, and stirred until the solids were fully dissolved to obtain a complexing agent solution (the concentration of disodium hydroxyethylidene diphosphonate in the complexing agent solution was 0.20 mol / L, the concentration of sodium citrate was 0.80 mol / L, the concentration of potassium pyrophosphate was 0.75 mol / L, and the concentration of sodium tetraborate was 0.1 mol / L). (0 mol / L); Under stirring, a mixed solution of copper sulfate and nickel sulfate was added to a complexing agent solution, followed by the addition of sodium saccharin and additives. The mixture was stirred until the solid was fully dissolved to obtain a deposition electrolyte. The concentrations of copper sulfate, nickel sulfate, disodium hydroxyethylidene diphosphonate, sodium citrate, potassium pyrophosphate, sodium tetraborate, sodium hydroxyethylidene diphosphonate, sodium saccharin, and additives in the deposition electrolyte were 0.04 mol / L, 0.15 mol / L, 0.04 mol / L, 0.16 mol / L, 0.15 mol / L, 0.02 mol / L, 1.0 g / L, and 0.1 g / L.

[0028] The preparation method of the additive is as follows: First, add 0.02 mol of 2-bromoethylphosphonic acid, 0.03 mol of anhydrous potassium carbonate, 0.5 g of potassium iodide, and 50 mL of anhydrous N,N-dimethylformamide to a 250 mL three-necked flask. Under nitrogen protection, stir at room temperature for 1 h to convert 2-bromoethylphosphonic acid into potassium phosphonate. Then, add 0.01 mol of benzo[1,2-d:4,5-d']bis(thiazole)-2,6 -Diamine was heated to 95℃ and stirred for 12 h. After the reaction was completed, it was cooled to room temperature, and the reaction solution was poured into 200 mL of deionized water. The pH was adjusted to 2 with 1 mol / L dilute hydrochloric acid, and a solid precipitated. The solid was filtered, and the filter cake was washed three times with deionized water (20 mL each time), and then washed twice with anhydrous ethanol (10 mL each time). The washed filter cake was dried in a vacuum drying oven at 50℃ to constant weight to obtain the bisphosphonic acid intermediate with a yield of 71%. The 1H NMR spectrum of the bisphosphonic acid intermediate is shown below. Figure 1 As shown, the chemical structure is as follows:

[0029] .

[0030] Then, in a 250 mL three-necked flask, add 0.01 mol of bisphosphonic acid intermediate, 0.022 mol of sodium 2-bromoethylsulfonate, 0.015 mol of anhydrous potassium carbonate, 0.5 g of potassium iodide, 50 mL of anhydrous N,N-dimethylformamide, and 10 mL of deionized water. Start stirring and heat to 85 °C under nitrogen protection, maintaining this temperature and stirring for 12 h. After the reaction is complete, cool to room temperature and add the reaction mixture dropwise to 500 mL of anhydrous ethanol while stirring. After the addition is complete, filter the mixture. Wash the filter cake twice with anhydrous ethanol (20 mL each time) to obtain the crude product. Dissolve the crude product in 80 mL of deionized water, adjust the pH to 2 with 1 mol / L dilute hydrochloric acid, precipitate a solid, filter, and rinse with deionized water pre-cooled to 2 °C. The filter cake was washed twice with deionized water (10 mL each time). The washed filter cake was then redissolved in 80 mL of deionized water. The pH was adjusted to 8 with 10% sodium hydroxide solution. The mixture was filtered, and the filtrate was concentrated by vacuum distillation at 60 °C to obtain a concentrate. 10 mL of deionized water was added to the concentrate, and the mixture was heated to 50 °C and stirred for 15 min. 120 mL of anhydrous ethanol was then added, and the mixture was heated to 80 °C and refluxed for 10 min. Heating was stopped, and the mixture was allowed to cool naturally to room temperature. It was then placed in an ice-water bath and cooled to 5 °C, held at that temperature for 3 h, and filtered. The filter cake was washed twice with anhydrous ethanol at 5 °C (15 mL each time). The washed filter cake was dried in a vacuum drying oven at 50 °C to constant weight to obtain the additive, with a yield of 56%. The 1H NMR spectrum of the additive is shown below. Figure 2 As shown, the chemical structure is as follows:

[0031] .

[0032] (2) Using a titanium plate as the cathode (20mm×50mm) and a phosphor bronze plate and a nickel plate as the anode (area ratio of 3:1), the deposited electrolyte is added to the electrolytic cell and heated to 60℃. The stirring speed is 400rpm and the current density is 1.0A / dm³. 2 Electrodeposition was performed under the specified conditions for 50 minutes. After electrodeposition, the titanium plate was removed, rinsed with deionized water, and dried. The copper-nickel alloy foil was then peeled off from the titanium plate. The average thickness of the copper-nickel alloy foil prepared in this embodiment was 6.5 μm, and the mass fraction of nickel in the copper-nickel alloy foil was 6.2%, with the balance being copper.

[0033] Example 2

[0034] The method for electrodepositing copper-nickel alloy foil using an organophosphonic acid and citric acid composite salt complex system in this embodiment includes the following steps:

[0035] (1) Dissolve copper sulfate and nickel sulfate in deionized water to obtain a mixed solution of copper sulfate and nickel sulfate (the concentrations of copper sulfate and nickel sulfate in the mixed solution are 0.25 mol / L and 0.60 mol / L, respectively); add disodium hydroxyethylidene diphosphonate, sodium citrate, potassium pyrophosphate and sodium tetraborate to deionized water, heat to 45~50℃, and stir until the solid is fully dissolved to obtain a complexing agent solution (the concentration of disodium hydroxyethylidene diphosphonate in the complexing agent solution is 0.24 mol / L, the concentration of sodium citrate is 0.96 mol / L, the concentration of potassium pyrophosphate is 0.90 mol / L, and the concentration of sodium tetraborate is 0.12 mol / L). (ol / L); Under stirring, a mixed solution of copper sulfate and nickel sulfate was added to the complexing agent solution, followed by the addition of sodium saccharin and additives. The mixture was stirred until the solid was fully dissolved to obtain the deposition electrolyte. The concentrations of copper sulfate, nickel sulfate, disodium hydroxyethylidene diphosphonate, sodium citrate, potassium pyrophosphate, sodium tetraborate, and additives in the deposition electrolyte were 0.05 mol / L, 0.12 mol / L, 0.048 mol / L, 0.192 mol / L, 0.180 mol / L, 0.024 mol / L, 1.5 g / L, and 0.25 g / L. The additives used in this example were the same as those in Example 1.

[0036] (2) Using a titanium plate as the cathode (20mm×50mm) and a phosphor bronze plate and a nickel plate as the anode (area ratio of 2:1), the deposition electrolyte is added to the electrolytic cell and heated to 65℃. The stirring speed is 450rpm and the current density is 1.2A / dm³. 2 Electrodeposition was performed under the specified conditions for 40 minutes. After electrodeposition, the titanium plate was removed, rinsed with deionized water, and dried. The copper-nickel alloy foil was then peeled off from the titanium plate. The average thickness of the copper-nickel alloy foil prepared in this embodiment was 5.8 μm, and the mass fraction of nickel in the copper-nickel alloy foil was 5.5%, with the balance being copper.

[0037] Example 3

[0038] The method for electrodepositing copper-nickel alloy foil using an organophosphonic acid and citric acid composite salt complex system in this embodiment includes the following steps:

[0039] (1) Dissolve copper sulfate and nickel sulfate in deionized water to obtain a mixed solution of copper sulfate and nickel sulfate (the concentrations of copper sulfate and nickel sulfate in the mixed solution are 0.15 mol / L and 0.90 mol / L, respectively); add disodium hydroxyethylidene diphosphonate, sodium citrate, potassium pyrophosphate and sodium tetraborate to deionized water, heat to 45~50℃, and stir until the solid is fully dissolved to obtain a complexing agent solution (the concentration of disodium hydroxyethylidene diphosphonate in the complexing agent solution is 0.16 mol / L, the concentration of sodium citrate is 0.72 mol / L, the concentration of potassium pyrophosphate is 0.70 mol / L, and the concentration of sodium tetraborate is 0.08 mol / L). (ol / L); Under stirring, a mixed solution of copper sulfate and nickel sulfate was added to the complexing agent solution, followed by the addition of sodium saccharin and additives. The mixture was stirred until the solid was fully dissolved to obtain the deposition electrolyte. The concentrations of copper sulfate, nickel sulfate, disodium hydroxyethylidene diphosphonate, sodium citrate, potassium pyrophosphate, sodium tetraborate, sodium hydroxyethylidene diphosphonate, sodium saccharin, and additives in the deposition electrolyte were 0.025 mol / L, 0.15 mol / L, 0.032 mol / L, 0.144 mol / L, 0.140 mol / L, 0.016 mol / L, 0.8 g / L, and 0.4 g / L. The additives used in this example were the same as those in Example 1.

[0040] (2) Using a titanium plate as the cathode (20mm×50mm) and a phosphor bronze plate and a nickel plate as the anode (area ratio of 4:1), the deposited electrolyte is added to the electrolytic cell and heated to 55℃. The stirring speed is 350rpm and the current density is 0.8A / dm. 2 Electrodeposition was performed under the specified conditions for 60 minutes. After electrodeposition, the titanium plate was removed, rinsed with deionized water, and dried. The copper-nickel alloy foil was then peeled off from the titanium plate. The average thickness of the copper-nickel alloy foil prepared in this embodiment was 7.2 μm, and the mass fraction of nickel in the copper-nickel alloy foil was 6.8%, with the balance being copper.

[0041] Comparative Example 1

[0042] The method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in this comparative example differs from the method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in Example 1 only in that no additives are added in step (1) of the method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in this comparative example, i.e., the concentration of additives in the deposition electrolyte is 0.

[0043] Comparative Example 2

[0044] The method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in this comparative example differs from the method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in Example 1 only in that the additive in step (1) of the method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in this comparative example is replaced with sodium 3-(2-benzothiazolyl-mercapto)propanesulfonate.

[0045] Comparative Example 3

[0046] The method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in this comparative example differs from the method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in Example 1 only in that the additive in step (1) of the method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in this comparative example is replaced with sodium 3-mercapto-1-propanesulfonate.

[0047] Comparative Example 4

[0048] The method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in this comparative example differs from the method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in Example 1 only in that the additive in step (1) of the method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in this comparative example is replaced with disodium bis(3-sulfopropyl)bis(benzothiazolyl-2-yl)disulfide.

[0049] Comparative Example 5

[0050] The method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in this comparative example differs from the method in Example 1 in that the preparation method of the additive in step (1) of the method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in this comparative example is as follows: 0.045 mol of 2-bromoethylphosphonic acid, 0.07 mol of anhydrous potassium carbonate, 1.0 g of potassium iodide, and 100 mL of anhydrous N,N-dimethylformamide are added to a 250 mL three-necked flask. Under nitrogen protection, the mixture is stirred at room temperature for 1 h to convert 2-bromoethylphosphonic acid into potassium phosphonate. Then, 0.01 mol of benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine is added to the three-necked flask. The mixture is heated to 95 °C and stirred for 18 h. After the reaction is complete, the mixture is cooled to room temperature, filtered, and the filtrate is distilled under reduced pressure at 70 °C. N,N-dimethylformamide was removed to obtain a crude product. The crude product was dissolved in 80 mL of deionized water, and the pH was adjusted to 2 with 1 mol / L dilute hydrochloric acid, precipitating a solid. The solid was filtered, and the filter cake was washed twice with deionized water pre-cooled to 2°C (10 mL each time). The washed filter cake was redissolved in 80 mL of deionized water, and the pH was adjusted to 8 with 10% sodium hydroxide solution. The solution was filtered, and the filtrate was concentrated by vacuum distillation at 60°C to obtain a concentrate. 10 mL of deionized water was added to the concentrate, and the mixture was heated to 50°C and stirred for 15 min. 120 mL of anhydrous ethanol was then added, followed by heating to 80°C and reflux with stirring for 10 min. Heating was stopped, and the mixture was allowed to cool naturally to room temperature. It was then placed in an ice-water bath and cooled to 5°C, kept at this temperature for 3 h, and filtered. The filter cake was washed twice with anhydrous ethanol at 5°C (15 mL each time). The washed filter cake was dried in a vacuum drying oven at 50°C to constant weight to obtain the additive. The chemical structure of the additive is as follows:

[0051] .

[0052] Comparative Example 6

[0053] The method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in this comparative example differs from the method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in Example 1 only in that the preparation method of the additive in step (1) of the method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in this comparative example is as follows: 0.01 mol of benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine, 0.045 mol of sodium 2-bromoethylsulfonate, 0.04 mol of anhydrous potassium carbonate, 1.0 g of potassium iodide, 100 mL of anhydrous N,N-dimethylformamide, and 2 g of potassium iodide are added to a 250 mL three-necked flask. Add 0 mL of deionized water, start stirring, heat to 85 °C under nitrogen protection, and maintain the temperature and stir for 18 h. After the reaction is complete, cool to room temperature, filter, and remove N,N-dimethylformamide by vacuum distillation at 70 °C to obtain the crude product. Dissolve the crude product in 30 mL of deionized water, add 2.0 g of sodium chloride and stir to dissolve. Then add 200 mL of anhydrous ethanol under stirring, precipitating a solid, which is then filtered. Redissolve the filter cake in 30 mL of deionized water, add 200 mL of anhydrous ethanol again to precipitate a solid, filter, and wash the filter cake twice with anhydrous ethanol (15 mL each time). Place the washed filter cake in a vacuum drying oven at 50 °C and dry to constant weight to obtain the additive. The chemical structure of the additive is as follows:

[0054] .

[0055] Comparative Example 7

[0056] The method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in this comparative example differs from the method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in Example 1 only in that the additive in step (1) of the method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in this comparative example is composed of the additives in Comparative Example 5 and Comparative Example 6 in a molar ratio of 1:1.

[0057] Comparative Example 8

[0058] The method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in this comparative example differs from the method in Example 1 in that the steps (1) of the method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in this comparative example are as follows: Copper sulfate and nickel sulfate are dissolved in deionized water to obtain a mixed solution of copper sulfate and nickel sulfate (the concentrations of copper sulfate and nickel sulfate in the mixed solution are 0.20 mol / L and 0.75 mol / L, respectively); sodium citrate, potassium pyrophosphate, and sodium tetraborate are added to deionized water, heated to 45~50℃, and stirred until the solids are fully dissolved to obtain a complexing agent solution (the complexing agent solution contains sodium citrate, potassium pyrophosphate, and sodium tetraborate). The concentrations of sodium citrate (0.224 mol / L), potassium pyrophosphate (0.210 mol / L), and sodium tetraborate (0.028 mol / L) were mixed. Under stirring, a solution of copper sulfate and nickel sulfate was added to the complexing agent solution, followed by the addition of sodium saccharin and additives. The mixture was stirred until the solids were fully dissolved to obtain the deposition electrolyte. The concentrations of copper sulfate, nickel sulfate, sodium citrate, potassium pyrophosphate, sodium tetraborate, sodium saccharin, and additives in the deposition electrolyte were 0.04 mol / L, 0.15 mol / L, 0.179 mol / L, 0.168 mol / L, 0.022 mol / L, 1.0 g / L, and 0.1 g / L, respectively.

[0059] Comparative Example 9

[0060] The method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in this comparative example differs from the method in Example 1 in that the steps (1) of the method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in this comparative example are as follows: Copper sulfate and nickel sulfate are dissolved in deionized water to obtain a mixed solution of copper sulfate and nickel sulfate (the concentrations of copper sulfate and nickel sulfate in the mixed solution are 0.20 mol / L and 0.75 mol / L, respectively); disodium hydroxyethylidene diphosphonate, potassium pyrophosphate, and sodium tetraborate are added to deionized water, heated to 45~50℃, and stirred until the solid is fully dissolved to obtain a complexing agent solution (the complexing agent solution contains disodium hydroxyethylidene diphosphonate). The concentrations of disodium bisphosphonate (0.088 mol / L), potassium pyrophosphate (0.330 mol / L), and sodium tetraborate (0.044 mol / L) were as follows: A mixed solution of copper sulfate and nickel sulfate was added to the complexing agent solution under stirring, followed by the addition of sodium saccharin and additives. The mixture was stirred until the solids were fully dissolved to obtain the deposition electrolyte. The concentrations of copper sulfate, nickel sulfate, disodium hydroxyethylidene bisphosphonate, potassium pyrophosphate, sodium tetraborate, and sodium saccharin in the deposition electrolyte were 0.04 mol / L, 0.15 mol / L, 0.070 mol / L, 0.264 mol / L, 0.035 mol / L, 1.0 g / L, and 0.1 g / L, respectively.

[0061] Comparative Example 10

[0062] The method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in this comparative example differs from the method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in Example 1 only in that step (1) of the method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in this comparative example is as follows: copper sulfate and nickel sulfate are dissolved in deionized water to obtain a mixed solution of copper sulfate and nickel sulfate (the concentrations of copper sulfate and nickel sulfate in the mixed solution are 0.20 mol / L and 0.75 mol / L, respectively); disodium hydroxyethylidene diphosphonate, sodium citrate and sodium tetraborate are added to deionized water, heated to 45~50℃, and stirred until the solid is fully dissolved to obtain a complexing agent solution (the complexing agent solution contains disodium hydroxyethylidene diphosphonate). The concentrations of disodium bisphosphonate (0.084 mol / L), sodium citrate (0.336 mol / L), and sodium tetraborate (0.043 mol / L) were as follows: A mixed solution of copper sulfate and nickel sulfate was added to the complexing agent solution under stirring, followed by the addition of sodium saccharin and additives. The mixture was stirred until the solids were fully dissolved to obtain the deposition electrolyte. The concentrations of copper sulfate, nickel sulfate, disodium hydroxyethylidene bisphosphonate, sodium citrate, sodium tetraborate, sodium saccharin, and additives in the deposition electrolyte were 0.04 mol / L, 0.15 mol / L, 0.067 mol / L, 0.269 mol / L, 0.034 mol / L, 1.0 g / L, and 0.1 g / L, respectively.

[0063] Comparative Example 11

[0064] The method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in this comparative example differs from the method in Example 1 in that the steps (1) of the method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in this comparative example are as follows: copper sulfate and nickel sulfate are dissolved in deionized water to obtain a mixed solution of copper sulfate and nickel sulfate (the concentrations of copper sulfate and nickel sulfate in the mixed solution are 0.20 mol / L and 0.75 mol / L, respectively); disodium hydroxyethylidene diphosphonate, sodium citrate, and potassium pyrophosphate are added to deionized water, heated to 45~50℃, and stirred until the solid is fully dissolved to obtain a complexing agent solution (the complexing agent solution contains hydroxyethylidene diphosphonate). The concentrations of disodium bisphosphonate (0.053 mol / L), sodium citrate (0.211 mol / L), and potassium pyrophosphate (0.199 mol / L) were as follows: A mixed solution of copper sulfate and nickel sulfate was added to the complexing agent solution under stirring, followed by the addition of sodium saccharin and additives. The mixture was stirred until the solids were fully dissolved to obtain the deposition electrolyte. The concentrations of copper sulfate, nickel sulfate, disodium hydroxyethylidene bisphosphonate, sodium citrate, potassium pyrophosphate, sodium saccharin, and additives in the deposition electrolyte were 0.04 mol / L, 0.15 mol / L, 0.042 mol / L, 0.169 mol / L, 0.159 mol / L, 1.0 g / L, and 0.1 g / L, respectively.

[0065] Comparative Example 12

[0066] The method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in this comparative example differs from the method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in Example 1 only in that sodium saccharin is replaced with sodium bis(benzenesulfonyl)imide in step (1) of the method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system in this comparative example.

[0067] Experimental Example

[0068] To evaluate the comprehensive performance of the copper-nickel alloy foils prepared by the electrodeposition methods of the various embodiments and comparative examples, the thickness uniformity, surface roughness, tensile strength, elongation, and corrosion current density of the copper-nickel alloy foils prepared by the various embodiments and comparative examples were tested. Simultaneously, to examine the stable performance of the deposition electrolyte used in the various embodiments and comparative examples, the continuous electroplating stability of the deposition electrolyte was tested. The thickness uniformity was tested as follows: thickness measurements were performed at 15 test points on each copper-nickel alloy foil to be tested (the 15 test points on different copper-nickel alloy foils to be tested were at the same locations). The average thickness was then calculated based on the test results. Finally, the ratio of the difference between the maximum and minimum thickness values ​​to the average thickness was calculated to obtain the thickness uniformity. The surface roughness was tested as follows: the surface roughness Ra of the alloy foil growth surface (i.e., the growth surface in contact with the electrolyte during electrodeposition) was measured using a surface profilometer. Five different locations were selected for testing for each sample, and the average value was taken. Tensile strength and elongation were tested using a universal tensile testing machine. Samples were cut into strips of 15mm × 100mm, and the tensile speed was 50mm / min. Five parallel samples were tested for each sample, and the average value was taken. The corrosion current density was tested using a three-electrode system: a copper-nickel alloy foil as the working electrode, a saturated calomel electrode as the reference electrode, and a platinum electrode as the counter electrode. The test was conducted in a 3.5 wt.% sodium chloride aqueous solution. First, Tafel polarization curves were measured using an electrochemical workstation at a scan rate of 0.01V / s, with a scan range of open circuit potential ±0.3V. Then, the corrosion current density was calculated using the Tafel extrapolation method. The test method for continuous electroplating stability is as follows: A continuous electroplating experiment was conducted in the electrolytic cell according to step (2) of Example 1. Samples were taken every 2 hours to analyze the plating solution composition (copper sulfate, nickel sulfate, disodium hydroxyethylidene diphosphonate, sodium citrate, potassium pyrophosphate, sodium tetraborate, sodium saccharin, and additives were added based on the analysis results to ensure the concentration of each component was controlled within ±2% of the initial value). Changes in cell voltage were observed. The process was continued for 72 hours. All cell voltage data recorded within 72 hours were statistically analyzed, and the difference between the maximum and minimum values, ΔV, was calculated. ΔV was used to evaluate the continuous electroplating stability; the larger the ΔV, the worse the stability of the continuous electroplating process. The test results for the thickness uniformity, surface roughness, tensile strength, elongation, corrosion current density, and continuous electroplating stability of the copper-nickel alloy foils prepared in each example and comparative example are shown in Table 1.

[0069] Table 1. Thickness uniformity, surface roughness, tensile strength, elongation, corrosion current density, and continuous electroplating stability of copper-nickel alloy foils with deposited electrolyte.

[0070] Copper-nickel alloy foil Thickness uniformity Surface roughness (μm) Tensile strength (MPa) Elongation (%) <![CDATA[Corrosion current density (μA / cm 2 )]]> ΔV(V) Example 1 0.013 0.09 694 6.3 1.68 0.8 Example 2 0.011 0.07 719 6.0 1.57 0.7 Example 3 0.016 0.11 685 6.6 1.82 0.9 Comparative Example 1 0.112 0.28 326 4.5 3.25 4.8 Comparative Example 2 0.085 0.22 375 5.3 2.68 3.9 Comparative Example 3 0.096 0.26 341 4.8 2.95 4.3 Comparative Example 4 0.068 0.18 394 5.6 2.38 3.2 Comparative Example 5 0.076 0.21 385 5.2 2.62 3.9 Comparative Example 6 0.073 0.20 390 5.4 2.55 3.8 Comparative Example 7 0.082 0.23 387 5.3 2.65 4.1 Comparative Example 8 0.045 0.15 458 5.9 2.12 3.0 Comparative Example 9 0.135 0.32 304 4.0 3.85 5.2 Comparative Example 10 0.128 0.30 321 4.2 3.58 5.0 Comparative Example 11 0.052 0.16 446 5.8 2.28 3.1 Comparative Example 12 0.028 0.12 672 5.7 1.94 1.8

[0071] As shown in Table 1, the copper-nickel alloy foils prepared in Examples 1-3 exhibit good thickness uniformity, surface roughness, tensile strength, elongation, and corrosion resistance. Examples 1-3 of this invention use synthesized benzobisthiazolyl diphosphonic acid disulfonic acid hexasodium salt as an additive. This additive molecule contains both phosphonic acid groups and sulfonic acid groups. The phosphonic acid groups effectively inhibit the disproportionation reaction; the sulfonic acid groups can be adsorbed onto the cathode surface, generating cathodic polarization, refining the grains, and improving the leveling properties of the coating. Both work together to effectively improve the coating quality and the stability of the plating solution. The test results from Examples 1-3 show that the concentration of the additive has a certain impact on the coating performance. When the additive concentration is moderate, the overall performance of the coating is optimal; when the additive concentration is too low, the grain refinement effect is insufficient, and the coating density decreases; when the additive concentration is too high, excessive adsorption may inhibit the normal discharge of metal ions, leading to a decrease in coating quality.

[0072] The deposition electrolyte in Comparative Example 1 contained no additives. Compared to Example 1, its coating exhibited reduced tensile strength, increased corrosion current density, and poorer solution stability. This indicates that without additives, the disproportionation reaction of cuprous ions during electrodeposition is difficult to suppress, leading to the formation of a large amount of copper powder in the solution, poor solution stability, and a coating with coarse grains, low density, and decreased mechanical and corrosion resistance.

[0073] Comparative Examples 2 and 3 used ZPS and MPS, respectively, instead of the additives synthesized in this invention. Compared with Example 1, the tensile strength and corrosion resistance of their coatings were reduced. This is because ZPS and MPS contain only sulfonic acid groups and not phosphonic acid groups, which cannot effectively stabilize the cuprous ion intermediate. The disproportionation reaction in the plating bath is difficult to be fully suppressed, resulting in a decrease in coating quality.

[0074] Comparative Example 4 used bisbenzothiazole disulfonate containing only sulfonic acid groups (without phosphonic acid groups) as an additive. Compared with Example 1, the tensile strength and corrosion resistance of the coating were reduced, and the stability of the plating solution was worse. This indicates that although additives containing only sulfonic acid groups have a certain leveling effect, they cannot effectively stabilize cuprous ions due to the lack of phosphonic acid groups, resulting in poor plating solution stability and poor mechanical and corrosion resistance of the coating.

[0075] Comparative Example 5 used a tetraphosphonate containing only phosphonic acid groups (excluding sulfonic acid groups) as an additive. Compared with Example 1, its coating showed reduced tensile strength and corrosion resistance, and a larger surface roughness. This indicates that although the additive containing only phosphonic acid groups can stabilize cuprous ions and inhibit disproportionation reactions, it cannot provide sufficient cathodic polarization and leveling effects due to the lack of sulfonic acid groups, resulting in poor coating smoothness and mechanical properties. Comparative Example 6 used a tetrasulfonate containing only sulfonic acid groups (excluding phosphonic acid groups) as an additive, and its performance was also poor. The above results indicate that the present invention uses an additive containing both phosphonic acid groups and sulfonic acid groups, where the phosphonic acid groups are responsible for stabilizing cuprous ions, inhibiting disproportionation reactions, and improving the stability of the plating solution, while the sulfonic acid groups can provide cathodic polarization, refine grains, and improve coating levelness.

[0076] Comparative Example 7 involved physically mixing a tetraphosphonic acid additive containing only phosphonic acid groups (Comparative Example 5) and a tetrasulfonic acid additive containing only sulfonic acid groups (Comparative Example 6) at a molar ratio of 1:1. Compared to Example 1, the coating of Comparative Example 7 exhibited decreased tensile strength, increased surface roughness, and poorer plating solution stability. This indicates that in the complex system of the present invention, the physical mixture in which phosphonic acid groups and sulfonic acid groups are respectively attached to different molecules does not improve the coating leveling, mechanical properties, and plating solution stability as effectively as the additive in which both functional groups are simultaneously attached to the same benzobisthiazole backbone molecule. This further indicates that in the complex system of the present invention, the bifunctional additive obtained by simultaneously bonding phosphonic acid groups and sulfonic acid groups to the same benzobisthiazole backbone molecule has a better effect on improving the coating leveling, mechanical properties, and plating solution stability than the additive in which only phosphonic acid groups are physically mixed with the additive in which only sulfonic acid groups are attached. This may be because the two functional groups on the same molecule have fixed relative spatial positions, which is conducive to their synergistic effect of stabilizing cuprous ions and cathodic polarization at the electrode / solution interface. In contrast, the two molecules diffuse and adsorb independently in a physical mixture, making it difficult to achieve the same synergistic effect.

[0077] The electrolyte in Comparative Example 8 did not contain disodium hydroxyethylidene diphosphonate; it used only sodium citrate, potassium pyrophosphate, and sodium tetraborate as complexing agents. Compared to Example 1, the tensile strength of the coating was reduced, the surface roughness increased, and the stability of the plating solution deteriorated. This is because the phosphonic acid groups in disodium hydroxyethylidene diphosphonate have a strong complexing effect on copper ions, effectively inhibiting the disproportionation reaction of cuprous ions. Without disodium hydroxyethylidene diphosphonate, copper ions in the plating solution underwent a certain degree of disproportionation, generating trace amounts of copper powder, leading to a decrease in coating density and plating solution stability. However, since potassium pyrophosphate and sodium citrate could still maintain the basic copper-nickel co-deposition framework, the coating did not completely deteriorate.

[0078] The electrolyte in Comparative Example 9 did not contain sodium citrate; it only used disodium hydroxyethylidene diphosphonate, potassium pyrophosphate, and sodium tetraborate as complexing agents. Compared to Example 1, its plating solution exhibited poor stability during electrodeposition, resulting in a coating with lower tensile strength, higher surface roughness, and deteriorated corrosion resistance. This is because sodium citrate has a complexing and depolarizing effect on nickel ions. The absence of sodium citrate disrupts the potential window for copper-nickel co-deposition, preventing effective complexation of nickel ions and leading to the formation of large amounts of hydroxide precipitates. This hinders the co-deposition process and degrades the coating quality.

[0079] The deposition electrolyte in Comparative Example 10 did not contain potassium pyrophosphate; it only used disodium hydroxyethylidene diphosphonate, sodium citrate, and sodium tetraborate as complexing agents. Compared with Example 1, the tensile strength of its coating decreased, and the stability of the plating solution deteriorated. Potassium pyrophosphate, as an auxiliary complexing agent, contributes to the stable complexation of nickel ions, the maintenance of the ionic strength of the plating solution, and the improvement of conductivity. Its absence not only alters the complexation environment of nickel, affecting the stability of co-deposition, but also changes the cathodic polarization behavior of the plating solution, leading to a decrease in plating solution stability and ultimately affecting the mechanical properties and corrosion resistance of the coating.

[0080] The deposition electrolyte in Comparative Example 11 did not contain sodium tetraborate; it only used disodium hydroxyethylidene diphosphonate, sodium citrate, and potassium pyrophosphate as complexing agents. Compared with Example 1, the tensile strength of the coating was reduced, and the stability of the plating solution was decreased. Sodium tetraborate, as a pH buffer, reduced the pH stability of the plating solution due to its absence, resulting in a decrease in both the stability of the plating solution and the performance of the coating.

[0081] In Comparative Example 12, sodium bis(benzenesulfonyl)imide was used instead of sodium saccharin in the deposition electrolyte. Compared with Example 1, the copper-nickel alloy foil prepared in Comparative Example 12 showed reduced tensile strength, elongation, and corrosion resistance, increased surface roughness and thickness uniformity, and decreased long-term operational stability of the plating solution. This may be because the sulfonamide structure in the sodium saccharin molecule has better compatibility with the organophosphonic acid complex system, which can more effectively eliminate the internal stress generated during the deposition of the copper-nickel alloy foil, thereby achieving better surface quality and plating solution stability while maintaining high strength.

[0082] In summary, this invention achieves a synergistic improvement in the high strength, high toughness, high corrosion resistance, and high plating solution stability of copper-nickel alloy foil by using an additive containing both phosphonic acid and sulfonic acid groups in a benzobisthiazole skeleton, combined with a composite complex system of disodium hydroxyethylidene diphosphonate-sodium citrate-potassium pyrophosphate-sodium tetraborate.

Claims

1. A method for electrodepositing copper-nickel alloy foil using an organophosphonic acid and citric acid composite salt complex system, characterized in that, Includes the following steps: An anode plate and a cathode plate are placed in a deposition electrolyte for electrodeposition to obtain a copper-nickel alloy foil on the cathode plate. The deposition electrolyte is prepared by mixing copper sulfate, nickel sulfate, disodium hydroxyethylidene diphosphonate, sodium citrate, potassium pyrophosphate, sodium tetraborate, sodium saccharin, additives, and water. The chemical structure of the additives is as follows: 。 2. The method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid composite salt complex system as described in claim 1, characterized in that, In the deposition electrolyte, the concentrations are as follows: copper sulfate 0.025–0.05 mol / L, nickel sulfate 0.12–0.15 mol / L, disodium hydroxyethylidene diphosphonate 0.03–0.05 mol / L, sodium citrate 0.12–0.18 mol / L, potassium pyrophosphate 0.12–0.18 mol / L, sodium tetraborate 0.015–0.025 mol / L, sodium saccharin 0.8–1.5 g / L, and additives 0.1–0.4 g / L.

3. The method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid composite salt complex system as described in claim 1, characterized in that... The electrodeposition process parameters are as follows: electrolyte temperature of 55~65℃, stirring speed of 350~450rpm, and current density of 0.8~1.2A / dm³. 2 .

4. The method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid composite salt complex system as described in claim 1, characterized in that, During electrodeposition, a titanium plate is used as the cathode, and a phosphor bronze plate and a nickel plate are used as the anode.

5. The method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid composite salt complex system as described in claim 4, characterized in that... The area ratio of the phosphor bronze plate to the nickel plate in the anode is 2~4:

1.

6. The method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system as described in any one of claims 1-5, characterized in that, The preparation method of the additive includes the following steps: 2-bromoethylphosphonic acid is mixed with potassium carbonate and potassium iodide in N,N-dimethylformamide to generate potassium phosphonate salt, and then benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine is added to react. The reaction product is acidified, washed and dried to obtain a bisphosphonic acid intermediate; the bisphosphonic acid intermediate is mixed with sodium 2-bromoethylsulfonate, potassium carbonate and potassium iodide in N,N-dimethylformamide containing water to obtain the additive.

7. The method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system as described in claim 6, characterized in that, The molar ratio of 2-bromoethylphosphonic acid, potassium carbonate, and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine is 2~2.1:3~3.5:

1.

8. The method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid complex salt system as described in claim 6, characterized in that, The reaction was carried out with benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine at a temperature of 90-100°C for 10-14 hours.

9. The method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid composite salt complex system as described in claim 6, characterized in that, The molar ratio of the bisphosphonic acid intermediate, sodium 2-bromoethylsulfonate, and potassium carbonate is 1:2.2~2.3:1.5~2.

10. The method for electrodepositing copper-nickel alloy foil using the organophosphonic acid and citric acid composite salt complex system as described in claim 6, characterized in that, The bisphosphonic acid intermediate was reacted with sodium 2-bromoethylsulfonate, potassium carbonate, and potassium iodide in N,N-dimethylformamide containing water at a temperature of 80-90°C for 10-14 hours.